(Eyewitness books) Bird - Burnie, David; Chadwick, Peter Taylor, Kim (Dorling Kindersley New York, 2000)
A photo essay on the world of birds examining such topics as body construction, feathers and flight, the adaptation of beaks and feet, feeding habits, courtship, nests and eggs, and bird watching